MODERN PACKAGING TECHNOLOGIES IN THE FOOD - Федорів, Віктор; Стечишин, Мирослав; Мартинюк, Андрій; Люховець, Володимир; Ткач, Богдан (SWorldJournal, 2025)
The article discusses modern packaging technologies in the food industry that determine the competitiveness of products and their compliance with sustainable development requirements. The main trends in the development of packaging materials and technical